THE EFFECT OF COOPERATIVE LEARNING MODEL GROUP INVESTIGATION AGAINST STUDENT LEARNING OUTCOMES PHYSICS VIEWED FROM THE ADVERSITY QUOTIENT - Rajo Hasim Lubis (Jurnal Pendidikan Fisika, 2017)
This study aims to determine: learning outcomes physics students with cooperative learning model GI and conventional learning, learning outcomes physics students who have Adversity Quotient (AQ) high and medium AQ and interaction cooperative learning model GI and AQ in affecting learning physics students.  This quasi-experimental study using pretest-posttest control group design. The sample in this research is class X IPA.4 as an experimental class and class X IPA.3 as the control class is selected by simple random sampling. The instrument used is the achievement test and which AQ questionnaire form. Data was analyzed using two ways  ANOVA. The results shows that: learning outcomes physics students with cooperative learning model GI better than conventional learning, learning outcomes physics students who have a high AQ better than students who have a medium AQ and there is interaction between cooperative learning model GI and AQ in influencing physics student learning outcomes.